Influence of age and disease severity on high resolution CT lung densitometry in asthma. Issue 11 (1st November 2001) - Mitsunobu, F; Mifune, T; Ashida, K; Hosaki, Y; Tsugeno, H; Okamoto, M; Harada, S; Takata, S; Tanizaki, Y
Abstract : BACKGROUND: Low attenuation areas (LAA) on computed tomographic (CT) scans have been shown to represent emphysematous changes in patients with chronic obstructive pulmonary disease (COPD). However, the significance of LAA is still controversial in patients with asthma. This study was undertaken to assess the usefulness of lung CT densitometry in the detection of airspace enlargement in association with asthma severity. METHODS: Forty five asthmatic subjects and 15 non-smoking controls were studied to determine the influence of age, pulmonary function, and asthma severity on mean lung density (MLD) and the relative area of the lung showing attenuation values less than –950 HU (RA950 ) on high resolution CT (HRCT) scans. RESULTS: In asthmatic patients both MLD and RA950 correlated with parameters of airflow limitation (%FEV1, FEV1 /FVC, %FEF25–75 ) and lung volume (%TLC, %FRC, %RV), but not with lung transfer factor (%Tlco, %Tlco /VA). The results of HRCT lung densitometry also correlated with patient age and severity of asthma. CONCLUSIONS: Decreased CT lung density in non-smoking asthmatics is related to airflow limitation, hyperinflation and aging, but not with lung transfer factor.